Number of Recent Sexual Partners among Blood Donors in Brazil: Associations with Donor Demographics, Donation Characteristics and Infectious Disease Markers - Patavino, Giuseppina Maria (2011)
BACKGROUND: Brazilian blood centers ask candidate blood donors about the number of sexual partners in the last 12 months. Candidates who report a number over the limit are deferred. We studied the implications of this practice on blood safety. STUDY DESIGN AND METHODS: We analyzed demographic characteristics, number of heterosexual partners, and disease marker rates among 689,868 donations from three Brazilian Centers between July 2007 and December 2009. Donors were grouped based on maximum number of partners allowed in the last 12 months for each center. Chi-square and logistic regression analysis were conducted to examine associations between demographic characteristics, number of sex partners, and individual and overall positive markers rates for HIV, HTLV-1/2, HBV, HCV, and syphilis. RESULTS: First-time, younger and more educated donors were associated with a higher number of recent sexual partners, as was male gender in São Paulo and Recife (p <0.001). Serologic markers for HIV, syphilis and overall were associated with multiple partners in São Paulo and Recife (p<0.001), but not in Belo Horizonte (p= 0.05, 0.94, 0.75, respectively). In logistic regression analysis, number of recent sexual partners were associated with positive serologic markers (AOR=1.2–1.5) especially HIV (AOR=1.0–4.4). CONCLUSIONS: Number of recent heterosexual partners was associated with HIV positivity and overall rates of serological markers of sexually transmitted infections. The association was not consistent across centers, making it difficult to define the best cut-off value. These findings suggest the use of recent heterosexual contacts as a potentially important deferral criterion to improve blood safety in Brazil.